In-service math teacher training workshops with technology integration: some examples - Bastos, Nuno R. O. (2022)
As teaching in not a static but a progressing, continuous and lifelong process and, as the quality of teachers is the key for effective learning, in-service teachers need to participate in continuous training. In-service teacher continuous training can, in few words, be defined as the set of activities that will improve and update in-service teachers' professional knowledge, skills, and competences. In Portugal, in-service teachers are required to undertake continuous training. Training actions take different forms such as: training courses, training workshops, study circles, short-term actions or, at the request of the Scientific and Pedagogical Council for Continuing Education (CCPFC), internships and projects. Since 1997 in the institution where I work, we organize, in a joint organization with the Centre Regional Delegation of the Portuguese Mathematical Society (SPM-Centro), in a regular basis, the "MatViseu", a meeting for Portuguese in-service teachers. The main purpose of "MatViseu" is to respond to the needs of updating and deepening the knowledge/skills of mathematics in-service teachers from elementary to secondary school. Along the years I have been invited to prepare some workshops at "MatViseu" were always exist two particular concerns from my side: one is to use free software/platforms and the other is to share some ideas and simple strategies to implement free software/platforms in classroom. On each workshop, as they are hands-on, it was only available for a maximum of 32 in-service teachers. The appropriate use of software in mathematics classes can, on one side be greatly useful to gather student's questions to exercises and on the other side can offer valuable support to provide and make clearer some mathematical concepts. At the end of each “MatViseu” edition in-service teachers need to make a report about each workshop and the feedback about these proposed workshops are very positive. Moreover, some of the teachers were participants in more than one of the workshops and when I asked if they implemented some of ideas of a previous workshop, they answers were positive. Even more, during training workshops, some of the teachers went beyond the proposed activities and create their own activities adapted to contents they teach. In this paper, for one hand, some of the workshop’s activities and ideas to implement them in the classroom will be presented and, for the other hand, will be mentioned few comments from in-service teachers who have been present.